PERTUMBUHAN SEMAI EBONI (Diospyros celebica Bakh.) PADA BERBAGAI INTENSITAS CAHAYA DAN JENIS MULSA - Harman, Harman; eardah, wardah; Zulkaidhah, Zulkaidhah (Jurnal Warta Rimba, 2019)
Ebony (Diospyros celebica Bakh.) Has a local name as kayu hitam, which is one of the superior tree species in Sulawesi. Ebony wood has a very high economic value because in addition to the beauty of fiber and wood color, ebony also includes exotic species that have high strength and durability. Ebony regeneration rate in nature is relatively low, this is caused by its semi-tolerant nature, where at the ebony seedling level requires shade plants. In addition to shade, mulch also plays an important role in the initial growth process of plants, the use of mulch is able to maintain a more stable soil temperature and is able to retain moisture around plant roots. The research was conducted for 3 months, from December 2015 to February 2016. The research location was in the area of the Faculty of Forestry, Tadulako University, Palu, Central Sulawesi Province. The method used is a completely randomized design (CRD) factorial pattern, which consists of two factors, namely light intensity and type of mulch. The materials used in this study were 6-month-old ebony seedlings, topsoil soil, bokashi fertilizer. Observation of ebony plant growth shows that ebony needs shade at an early stage and requires mulch for the growth process, I1M1 treatment (70% light intensity + 1kg coconut shell charcoal mulch) produces the best height increase of 1.79 cm. The I1M2 treatment (70% light intensity + 1kg sawdust charcoal mulch), the best is 1.30 mm. The I2M1 treatment (90% light intensity + 1kg coconut shell charcoal mulch) did not dominate the growth of leaves much as well as the I2M2 treatment (light intensity 90 + sawdust charcoal) did not dominate the leaf area increase.Keywords: Eboni, light intensity, mulch. Diospyros celebica Bakh